Изменение уровня молекул средней массы в сыворотке крови у больных химиорезистентным туберкулезом легких - Разнатовская, Е. Н.; Разнатовська, Олена Миколаївна; Raznatovska, E. N. (Запорізький державний медичний університет, 2012)
В сыворотке крови больных химиорезистентным туберкулезом легких констатировано повышение уровня молекул средней массы. На основании полученных данных предложено использовать тест определения уровня молекул средней массы в сыворотке крови в качестве дополнительного биохимического критерия оценки прогноза развития химиорезистентного туберкулеза легких. In patients with drung-resistant a pulmonary tuberculosis diagnosed by raising the average weight of the molecules. Based on these data suggested the use of the defi nition of average weight molecules in serum as an additional criterion for the biochemical prediction of drung-resistant a pulmonary tuberculosis.
Changing of molecules of average weight in the blood in patients with drung-resistant a pulmonary tuberculosis
Keywords: молекулы средней массы; химиорезистентный туберкулез легких; molekuls the average weight; drung-resistant a pulmonary tuberculosis